Spatiotemporal characteristics of diesel exhaust particle pollution in confined space and impacts of ventilation and airflow: A laboratory simulation study - Zheyu HUANG; Jian ZHANG; Lihua HE; Wenchu HUANG; Zihui LI; Bilige HASEN; Hongbo WANG; Yun WANG (环境与职业医学)
BackgroundDiesel engines are widely used in transportation, agriculture, construction, industry, and other fields. Diesel exhaust, classified as a Group 1 carcinogen, emits particles (DEP) that can penetrate deep into the respiratory tract, posing significant health risks. DEP pollution is particularly severe in confined environments, necessitating effective control measures.ObjectiveUnder laboratory simulation conditions, to explore the spatiotemporal distribution characteristics of the mass and number concentrations of DEP as it diffuses indoors and to reveal the effects of ventilation and additional airflow on indoor DEP pollution levels.MethodsA diesel engine was placed in a laboratory (length 3.39 m × width 2.85 m × height 2.4 m) with its exhaust emitted from east to west. An air purifier was installed 1 m south of the engine. Eight measurement points (1 m horizontal distance from the exhaust outlet, height: 1 m/1.5 m) were setup to monitor DEP concentrations using portable laser particle sizers. The effects of engine power (4.05 kW vs. 5.15 kW), ventilation (maximum airflow: 600 m3·h−1), additional airflow intensity (low and high), and direction (forward/reverse) on DEP pollution were analyzed. DEP levels of 5 diesel vehicle models were also compared.ResultsThe mass and number concentrations of DEP indoors increased immediately after the diesel engine started. The peak mass concentration time at the eastern measurement point (−1, 0) m opposite to the exhaust direction (17.70 min) was significantly longer than that at the western (1, 0) m (16.20 min), southern (0, -1) m (14.45 min), and northern (0, 1) m (12.70 min) points (P<0.05), with no significant differences between the other points (western, southern, and northern) (P>0.05). The northern point (0, 1) m exhibited the highest DEP mass and number concentration peaks (174.62 μg·m−3, 1319.85 p·cm−3), significantly exceeding those at the southern (0, −1) m (129.89 μg·m−3, 1175.24 p·cm−3), eastern (−1, 0) m (140.12 μg·m−3, 1120.53 p·cm−3), and western (1, 0) m (147.60 μg·m−3, 818.62 p·cm−3) points (P<0.05), and no significant differences were observed among other points (P>0.05). There were no significant differences in peak DEP mass and number concentrations by measurement heights (P>0.05). Diesel engine power, ventilation, airflow intensity, and airflow direction had no significant effect on the time of peak DEP concentration (P>0.05). However, higher engine power (5.15 kW) produced greater DEP peaks [(186.66±19.29) μg·m−3, (1382.79±122.56) p·cm−3] than the 4.05 kW engine power [(168.41±12.65) μg·m−3, (1284.45±71.30) p·cm−3] (P<0.05). The peak mass concentration [(342.04±35.03) μg·m−3] and number concentration [(1886.87±57.91) p·cm−3] of DEP in the non-ventilated group were significantly higher than those in the ventilated group [(186.66±19.29) μg·m−3, (1382.79±122.56) p·cm−3] (P<0.001). Forward airflow elevated DEP mass concentrations compared to reverse airflow (287.71 μg·m−3 vs. 243.74 μg·m−3, t=−2.592, P=0.009), but no effects on DEP number concentration (P>0.05). Significant differences in mass concentration were observed among selected 5 vehicle models (Z=38.109, P<0.001).ConclusionThe operation of diesel engines will emit a large amount of particulate matter, causing pollution in enclosed spaces. Diesel engines with greater power have higher levels of DEP pollution emissions. Based on the spatiotemporal distribution characteristics, it is recommended to set the operation position in the reverse direction of exhaust emissions and close to air purifiers, while avoiding the use of additional air flow equipment.